Familiarity and strangeness: Seeing everyday practices of punishment and resistance in Holloway Prison - Guest, Carly (Punishment & society, 2020)
London’s Holloway Prison, the largest women’s prison in western Europe, closed in 2016. The impact of the closure on the women incarcerated in Holloway, and the prison’s place in the local community, is the focus of a project led by Islington Museum. Here, we develop an innovation, emotion-led methodology to explore photographs of the decommissioned Holloway, asking what they communicate about experiences of imprisonment and practices of punishment. The images illustrate the strategies of control, mechanisms of punishment and tactics of resistance that operate through the carceral space. From a feminist, anti-carceral perspective, we emphasise the importance of seeing prison spaces and attending to the emotional responses generated. We offer a creative intervention into dominant government and media narratives of Holloway’s closure and suggest that considering what it is that feels familiar and strange about carceral spaces has the potential to operate as a form of anti-carceral work.